Decolonising the university curriculum - Le Grange, L (South African Journal of Higher Education, 2016)
The student protests of 2015 precipitated a renewed interest in the decolonisation of the university in South Africa, and by association the decolonisation of the university curriculum. The decolonisation of the curriculum is an important conversation, and long overdue, given that the Western model of academic organisation on which the South African university is based, remains largely unchallenged. In this article I add to the conversation by discussing what decolonisation entails, why the need for decolonisation, the importance of rethinking how curriculum is conceived, and outlining some possible ways of decolonising the university curriculum. The purpose is not to provide a set of answers but to open up ways of (re)thinking the university curriculum.